Case 3789: Ateuchus costatus Wiedemann, 1823 (currently Scarabaeus costatus) (Insecta, Coleoptera, Scarabaeidae): proposed conservation of the specific name - Daniel, Gimo M; Cupello, Mario (Bulletin of Zoological Nomenclature, 2019)
The purpose of this application, under Article 23.9.5 of the Code, is to conserve the specific name Ateuchus costatus Wiedemann, 1823, a junior primary homonym of Ateuchus costatus Thunberg, 1818. These names are currently in use and have not been treated as congeneric since 1869, when the homonyms were transferred to the genera Scarabaeus Linnaeus, 1758 and Sisyphus Latreille, 1807, respectively. It is highly unlikely that these names will be considered congeneric in the future. Therefore, it is proposed that Ateuchus costatus Wiedemann, 1823 be conserved by ruling that it is not invalid by reason of being a primary junior homonym of Ateuchus costatus Thunberg, 1818. Noticed in BZN 76 (30 April 2019): 2.
Keywords: Nomenclature; taxonomy; Insecta; Coleoptera; Scarabaeidae; Scarabaeinae; Scarabaeini; Sisyphini; Ateuchus; Scarabaeus; Sisyphus; Scarabaeus costatus; Sisyphus costatus; dung beetles; Afrotropical Region